2015
DOI: 10.1044/2015_aja-15-0021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Amplification on Speech and Language in Children With Aural Atresia

Abstract: Our findings highlight a relationship between side of atresia, time of first amplification, compliance in aid use, and speech and language abilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Many previous studies investigating audiological outcome in patients with atresia of the auditory canal only report on a follow-up period after initial fitting, which means approximately six weeks after implantation. [ 3 , 9 , 26 28 ] or up to 3 or 6 months after implantation [ 29 31 ]. Hempel et al [ 32 ] and Mandala [ 33 ] reported long-term results up to 36 months and 41.7 ± 18.6 months on average, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many previous studies investigating audiological outcome in patients with atresia of the auditory canal only report on a follow-up period after initial fitting, which means approximately six weeks after implantation. [ 3 , 9 , 26 28 ] or up to 3 or 6 months after implantation [ 29 31 ]. Hempel et al [ 32 ] and Mandala [ 33 ] reported long-term results up to 36 months and 41.7 ± 18.6 months on average, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Independent of the onset of unilateral hearing loss (congenital or acquired), associated difficulties in directional hearing or speech recognition in noisy environments can affect the quality of life [ 2 ]. In particular, children with congenital aural atresia may have impairments in speech and language development, and consequently may perform poorly in school [ 3 ]. There are studies that show a positive relationship between the time of first hearing amplification by hearing devices, compliance in aid use, speech and language abilities, and general development of children [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it has been suggested that early treatment with a BCD might be more beneficial than implantation later in life (Attaway et al, 2015;Liu et al, 2017). In general, there is consensus that hearing rehabilitation should start sooner rather than later in life (Cremers et al, 2010).…”
Section: Introductionmentioning
confidence: 99%